Inflammatory indices as an indicator of acute pancreatitis severity - Uslu, Muhammed Fuad; Timurkaan, Esra; Timurkaan, Mustafa; Yilmaz, Mustafa (My University, 2025)
Objective: The present study aimed to compare C-reactive protein (CRP), neutrophil/lymphocyte ratio (NLR), neutrophil/albumin ratio (NAR), platelet/leukocyte ratio (PLR), systemic immune inflammation (SII), systemic inflammation response index (SIRI) and Ranson criteria associated with inflammation in acute pancreatitis (AP). Thus, the study aimed to analyze the significance ranking of these parameters in terms of disease severity. Method: The present retrospective study was conducted after the ethics committee approval was obtained. The study included 221 AP patients visited hospital between 01.01.2018 and 31.12.2023. The patients were categorized into two groups based on Ranson criteria: Group 1 (Ranson?2, n=147) and Group 2 (Ranson?3, n=74). Basic participant demographics, laboratory reports, CRP, NLR, NAR, PLR, SII, SIRI and hospitalization periods were recorded in a data form, and the findings were analyzed. Results: There was no difference between the groups based on gender (p=0.094). The Group 2 patients were older (p<0.001) than the ones in Group 1. Furthermore, CRP (p=0.001), NLR (p<0.001), NAR (p<0.001), PLR (p<0.001), SII (p<0.001) and SIRI (p<0.001) were higher in Group 2 patients when compared to Group 1. Also, the hospitalization period was significantly longer in Group 2 (p<0.001) compared to Group 1. Conclusion: In the study, it was determined that the CRP, NAR, PLR, NLR, SII and SIRI findings were significantly higher in AP patients with a Ranson criteria ? 3, and a positive correlation was found between Ranson criteria and inflammatory parameters.
Keywords: Acute pancreatitis; hematological parameters; systemic inflammation response index; systemic immune inflammation